A study on the relationship between job satisfaction and employee performance in MARA HQ / Mismawarusmaryati Abdul Aziz - Abdul Aziz, Mismawarusmaryati (Faculty of Business and Management, 2010)
This research is about the study on the relationship between job satisfaction and employee performance in Majlis Amanah Rakyat in the Head Quarters in Kuala Lumpur. There are a few elements that contributed to the employee job satisfaction, and three of them are compensation and benefits, motivation and support from the superior, and training. The survey is conducted in the Head Quarters of Majlis Amanah Rakyat, Jalan Raja Laut, Kuala Lumpur. The sample size is about 100 respondents who are selected randomly. The data collection method that was used are primary and secondary data which is by questionnaire as the primary data, while journal and internet sources as the secondary data. After the data has been collected, the Statistical Package for the Social Science (SPSS) version 16.0 been used in order to analyze the data. The result is in the form of reliability test, frequency, and also correlation. From the result that has been gathered, it shows that there is significant relationship between the independent variables and dependent variables. Besides that, there are also recommendations in order to improve the level of job satisfaction and performance of the employee.